Indicadores De Resultados Universitarios: Un Estudio De Métodos Mixtos - De La Rosa, Olga María Alegre; Angulo, Luis Miguel Villar (European Scientific Journal, ESJ, 2018)
In this study, university performance indicators (students’ success rates, efficiency, graduation, dropout and attainment) of different fields of knowledge are analyzed to compare them with the opinion of the quality commissions of the different university centers. Mixed methods were used: a quantitative analysis of percentage means of the different fields of knowledge for the five university performance indicators and a qualitative analysis by means of a SWOT (weaknesses, threats, strengths and opportunities) with the opinion of the quality commissions in six dimensions of content: training program, infrastructure and resources, students, teachers, and institutional elements. Health Sciences are shown as the only branch of knowledge that improves the success rate in three years, however Social Sciences and Law and Engineering and Architecture improve efficiency. The Arts and Humanities branch has the highest dropout rate. We find similarities with other studies in the success rates improvement in Health Sciences, which contrasts with the dropout rates of Engineering and Architecture, as well as the low rate of graduation in the History of Art degree. It is proposed a longitudinal review of the instructional methods, training in university teaching and a plan for improvement student learning progress and enhancing performance of trainees.